A molecular model for drug binding to tandem repeats of telomeric G-quadruplexes. (20th May 2009) - Haider, Shozeb M.; Neidle, Stephen
Abstract : The extreme 3′-ends of human telomeres consist of 150–250 nucleotides of single-stranded DNA sequence together with associated proteins. Small-molecule ligands can compete with these proteins and induce a conformational change in the DNA to a four-stranded quadruplex arrangement, which is also no longer a substrate for the telomerase enzyme. The modified telomere ends provide signals to the DNA-damage-response system and trigger senescence and apoptosis. Experimental structural data are available on such quadruplex complexes comprising up to four telomeric DNA repeats, but not on longer systems that are more directly relevant to the single-stranded overhang in human cells. The present paper reports on a molecular modelling study that uses Molecular Dynamics simulation methods to build dimer and tetramer quadruplex repeats. These incorporate ligand-binding sites and are models for overhang–ligand complexes.